Enhancing the Zakat Framework of Maldives: A One Hundred Percent Muslim Country - Aishath Muneeza (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Maldives is a one hundred percent Muslim nation where the zakat administrative function is entrusted to a government ministry, the Ministry of Islamic Affairs (MIA), which manages zakat al maal and zakat al-fitr. Since June 1, 2016, MIA has delegated the task of collecting zakat to the Maldives Inland Revenue Authority (MIRA). Maldives presently has no law dealing with zakat, so the Islamic Training and Research Institute (IRTI) has proposed a set of zakat laws that could be adopted by the country. The objective of this qualitative research is to discuss the zakat framework proposed by IRTI. There is limited literature available on the zakat framework in Maldives, so it is anticipated that this study will become the starting point for further research on this topic.